2008
DOI: 10.1152/ajpcell.00422.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor PU.1 is expressed in white adipose and inhibits adipocyte differentiation

Abstract: PU.1 transcription factor is a critical regulator of hematopoiesis and leukemogenesis. Because PU.1 interacts with transcription factors GATA-2 and C/EBPα, and both are involved in the regulation of adipogenesis, we investigated whether PU.1 plays a role in the regulation of adipocyte differentiation. Our data indicate that PU.1 is expressed in white adipose tissue. PU.1 protein can also be detected in cultured 3T3-L1 adipocytes. Forced expression of PU.1 in 3T3-L1 cells inhibits adipocyte differentiation, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 51 publications
6
59
0
Order By: Relevance
“…Future work should concentrate on understanding the molecular mechanism through which ETS-5 controls body fat storage/metabolism through the action of neuropeptides, and how satiety signals control locomotion and feeding. Multiple ETS TFs have been linked to obesity in humans (57)(58)(59)(60), and thus the important role of the ETS-5 TF that we describe here may be conserved in higher organisms as well.…”
Section: Discussionmentioning
confidence: 83%
“…Future work should concentrate on understanding the molecular mechanism through which ETS-5 controls body fat storage/metabolism through the action of neuropeptides, and how satiety signals control locomotion and feeding. Multiple ETS TFs have been linked to obesity in humans (57)(58)(59)(60), and thus the important role of the ETS-5 TF that we describe here may be conserved in higher organisms as well.…”
Section: Discussionmentioning
confidence: 83%
“…2A, compared with the control adipocytes expressing a scrambled shRNA, PU.1 shRNA-expressing adipocytes exhibit a 90% decreased PU.1 protein amount. Previously, we reported that overexpression of PU.1 suppresses adipogenesis (70). Here, downregulation of PU.1 expression enhanced adipocyte differentiation when the 3T3-L1 preadipocytes were differentiated under conventional conditions with exposure to a mixture of IBMX, dexamethasone, and insulin for 2 days and then insulin alone for another 4 days.…”
Section: Pu1 Is Expressed In the Adipocytes Of Obese Micementioning
confidence: 82%
“…Gonadal fat pads from A vy and lean control mice were minced in Krebs-Ringer phosphate buffer and digested with 1 mg/ml collagenase type I (Worthington Biochemical) at 37°C for 1 h, as described previously (70). Digested tissue was filtered through a nylon mesh and centrifuged at 500 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations